2022
DOI: 10.3390/genes14010013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs, circRNAs and Their Interactions in Development and Progression of Hepatocellular Carcinoma: An Insilico Approach

Abstract: Hepatocellular carcinoma (HCC) is a type of malignant tumor. miRNAs are noncoding RNAs and their differential expression patterns are observed in HCC-induced by alcoholism, HBV and HCV infections. By acting as a competing endogenous RNA (ceRNA), circRNA regulates the miRNA function, indirectly controlling the gene expression and leading to HCC progression. In the present study, data mining was performed to screen out all miRNAs and circRNA involved in alcohol, HBV or HCV-induced HCC with statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 170 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Extensive research has focused on understanding the roles and modifications of miRNAs in cancer development and progression, with potential implications for significant clinical and therapeutic advancements in molecular research. Additionally, in vitro studies highlight miRNAs as promising candidates for molecular replacement therapy, offering potential avenues to hinder cancer progression, prevent lymph node metastasis, and induce tumor cell apoptosis [ 282 , 283 ]. Furthermore, every investigation into miRNAs advances our understanding of the molecular mechanisms underlying oncogenesis and neurodegenerative disorders.…”
Section: Future Perspectives Regarding the Interaction Between Stress...mentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive research has focused on understanding the roles and modifications of miRNAs in cancer development and progression, with potential implications for significant clinical and therapeutic advancements in molecular research. Additionally, in vitro studies highlight miRNAs as promising candidates for molecular replacement therapy, offering potential avenues to hinder cancer progression, prevent lymph node metastasis, and induce tumor cell apoptosis [ 282 , 283 ]. Furthermore, every investigation into miRNAs advances our understanding of the molecular mechanisms underlying oncogenesis and neurodegenerative disorders.…”
Section: Future Perspectives Regarding the Interaction Between Stress...mentioning
confidence: 99%
“…Furthermore, every investigation into miRNAs advances our understanding of the molecular mechanisms underlying oncogenesis and neurodegenerative disorders. Recent research underscores the significance of exploring miRNAs and their target genes for their prospective contributions to personalized treatment strategies across diverse diseases [ 279 , 282 , 283 ].…”
Section: Future Perspectives Regarding the Interaction Between Stress...mentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are molecules that respond to stress; in this context, we note that physiological stress causes dysregulation in the expression of miRNAs, showing a higher prevalence in the central amygdala as well as in the hippocampus. In addition, chronic stress results in dysregulation of miRNAs in the frontal cortex, causing depression and neurodegenerative diseases [46][47][48][49][50][51][52]. A study realized by Qinlin.…”
Section: Studies On Microrna 129-5-p In Neurological Diseases and Dep...mentioning
confidence: 99%
“…Previous research has shown that a great quantity of miRNAs are aberrantly expressed in various cancer cell lines and tissues, and they participate in the biological processes such as the tumor invasion, metastasis, autophagy, regulation of the tumor microenvironment, chemotherapy resistance, and immunotherapy modulation[ 8 - 12 ]. As competitive endogenous RNAs, long noncoding RNAs (lncRNAs) and circRNAs contain miRNA binding sites and promote miRNA target gene expression through competition with miRNAs[ 13 - 17 ]. For example, Wang et al [ 18 ] identified and verified a novel MAGI2-AS3/miRNA-374-5p/FOXO1 network that was associated with HBV-related HCC.…”
Section: Introductionmentioning
confidence: 99%